The United States and the question of Western Sahara: A low priority in US Foreign Policy - Zoubir, Yahia H. (Africana Studia, 2020)
The protracted conflict in Western Sahara receives little attention from the United States. During the Cold War, although regional in nature, the United States had looked at the conflict as part of the East-West confrontation, which explains why the US perceived it as part of the confrontation against nationalist and communist movements worldwide. In principle, the United States is favorable to the principle of self-determination, a legitimate right of the Saharawis, victims of Spanish colonization and, since 1975, of Moroccan occupation. However, because of its strong ties to Morocco, an important ally in the Middle East and North Africa region, the United States has provided considerable support to Morocco’s illegal occupation of the disputed territory. In 2007, the US assisted Morocco in promoting the (illegal) notion of “autonomy” for Western Sahara, which serves as concealment for Morocco’s quasi-annexation of Western Sahara. This article analyzes the evolution of US policy toward the Western Sahara conflict; the main argument is that, despite its ambivalence, due to the vicissitudes of regional and international developments, the United States has not only continued its backing of Morocco but also that the conflict ranks very low in US foreign policy priorities. Keywords: Western Sahara, United States, decolonization, Morocco.